IMPROVING CHILDREN'S FINE MOTOR SKILLS AT THE AGE OF 4 - 5 YEARS THROUGH CHARCOAL FINGER PAINTING ACTIVITIES - Choirun Nisak Aulina (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Fine motor skills are an important ability for children to have. This research aims to improve the fine motor skills of children aged 4-5 years through charcoal finger painting activities. The research method used is the Class Action Research Method (PTK) which is carried out through 4 stages, namely planning, implementation and observation, reflection. The research subjects were 20 group A students at RA Ar-Rohmah. The data collection technique uses observation and documentation with a target of 75% success as seen in the child's ability in 1) eye and hand coordination, 2) finger strength, 3) wrist flexibility. The results of the research showed that there was an increase in the pre-cycle, the results were 47.5%, the results in cycle 1 were 72.5% and the results were 83.5% in cycle II, which means that charcoal finger painting activities can improve children's fine motor skills.